Differences and similarities in non-cystic fibrosis bronchiectasis between developing and affluent countries - KARADAĞ, BÜLENT TANER (ELSEVIER SCI LTD, 2011)
Non-CF bronchiectasis remains a major cause of morbidity not only in developing countries but in some indigenous groups of affluent countries. Although there is a decline in the prevalence and incidence in developed countries, recent studies in indigenous populations report higher prevalence. Due to the lack of such data, epidemiological studies are required to find the incidence and prevalence in developing countries. Although the main characteristics of bronchiectasis are similar in developing and affluent countries, underlying aetiology, nutritional status, frequency of exacerbations and severity of the disease are different. Delay of diagnosis is surprisingly similar in the affluent and developing countries possibly due to different reasons. Long-term studies are needed for evidence based management of the disease. Successful management and prevention of bronchiectasis require a multidisciplinary approach, while the lack of resources is still a major problem in the developing countries. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Bronchiectasis; children; epidemiology; diagnosis; management; SUPPURATIVE LUNG-DISEASE; NON-CF BRONCHIECTASIS; PEDIATRIC BRONCHIECTASIS; PULMONARY-FUNCTION; ORPHAN DISEASE; NEW-ZEALAND; CHILDREN; CHILDHOOD; ETIOLOGY; FEATURES